A Prospective Observational Study on Effect of Short‐Term Periodic Steroid Premedication on Bone Metabolism in Gastrointestinal Cancer (ESPRESSO‐01). (24th March 2017) - Nakamura, Michio; Ishiguro, Atsushi; Muranaka, Tetsuhito; Fukushima, Hiraku; Yuki, Satoshi; Ono, Kota; Murai, Taichi; Matsuda, Chika; Oba, Ayane; Itaya, Kazufumi; Sone, Takayuki; Yagisawa, Masataka; et al.
Abstract: Background: A multicenter prospective observational study evaluated the effect of gastrointestinal cancer chemotherapy with short‐term periodic steroid premedication on bone metabolism. Patients and Methods: Seventy‐four patients undergoing chemotherapy for gastrointestinal cancer were studied. The primary endpoints were changes in bone mineral densities (BMDs) and metabolic bone turnover 16 weeks after initiation of chemotherapy. BMDs, measured by dual‐energy x‐ray absorptiometry, and serum cross‐linked N‐telopeptides of type I collagen (sNTX), and bone alkaline phosphatase (sBAP) were assessed for evaluation of bone resorption and formation, respectively. Results: In 74.3% (55/74) of the patients, BMDs were significantly reduced at 16 weeks relative to baseline. The percent changes of BMD were −1.89% (95% confidence interval [CI], −2.67% to −1.11%: p  < .0001) in the lumbar spine, −2.24% (95% CI, −3.59% to −0.89%: p  = .002) in the total hip, and −2.05% (95% CI, −3.11% to −0.99%: p  < .0001) in the femoral neck. Although there was no significant difference in sNTX levels during 16 weeks ( p  = .136), there was a significant increase in sBAP levels ( p  = .010). Decreased BMD was significantly linked to number of chemotherapy cycles ( p  = .02). There were no significant correlations between changes in BMDs and the primary site of malignancy, chemotherapy regimens, total cumulative steroid dose, steroid dose intensity, and additive steroid usage. Conclusion: Gastrointestinal cancer chemotherapy with periodic glucocorticoid premedication was associated with reduced BMD and increased sBAP levels, which were linked to number of chemotherapy cycles but independent of primary site, chemotherapy regimen, duration, and additive steroid usage. Implications for Practice: Bone health and the management of treatment‐related bone loss are important for cancer care. The present study showed that a significant decrease in bone mineral density (BMD) and an increase in serum bone alkaline phosphatase levels occurred in gastrointestinal cancer patients receiving chemotherapy, which were linked to number of chemotherapy cycles but were independent of primary site, chemotherapy regimen, total steroid dose, and steroid dose intensity. Surprisingly, it seems that the decreasing BMD levels after only 16 weeks of chemotherapy for gastrointestinal cancer were comparable to that of 12‐month adjuvant aromatase inhibitor therapy for early‐stage breast cancer patients. Abstract : This study is an evaluation of the effect of gastrointestinal cancer chemotherapy with short‐term periodic steroid premedication on bone metabolism. Primary endpoints were changes in bone mineral densities and metabolic bone turnover 16 weeks after initiation of chemotherapy.